Cascaded optical polymer waveguide for enhanced fluorescence evanescent wave spectroscopy. (March 2020) - Abdul-Hadi, Jalal; Gauthier, Marc A.; Packirisamy, Muthukumaran
Highlights: Increased sensitivity of optical biosensing with cascaded waveguide. Detection limit as low as 9 pg/mL of Biotin-Alexa 647. Optical design optimization of the cascaded waveguide with beam propagation method. Abstract: A cascaded waveguide optical biosensor was developed for enhancing the sensitivity of evanescent wave fluorescence spectroscopy by increasing the area of analyte immobilization. Analysis of the coupled excitation and fluorescence light guided through the sensor was performed by numerical simulations with the beam propagation method and experimental characterization. A fluorescence evanescent wave spectroscopy experiment was done with Alexa 647-labeled biotin as the model analyte, and showed a sensitivity increase of 1.39 fold for the cascaded waveguide design compared to a single waveguide. Also, concentrations of biotin-Alexa 647 fluor/PBS solutions as low as 14.62 pg/mL and 8.88 pg/mL were detected for single and cascaded waveguides respectively.